Análisis jurídico del error de prohibición como causal de inculpabilidad en la legislación ecuatoriana - Aguirre Páez, María Sol (2024)
In Ecuador the legal institution of the prohibition error was incorporated in the reform of the Organic Integral Penal Code in 2019, it has its link with the theory of crime of 2014, with this legislation guilt is created as a requirement of knowledge of the unlawfulness of the conduct, that is, the person who commits any offense must have full knowledge of the legal rules prohibiting such act. If it is the case that a person commits an unlawful act in ignorance of the law, criminal dogmatics expresses that such person would be acting under a prohibition error, he/she believes that such act is lawful. This error can be overcome and invincible and these elements have their benefits. However, in the criminal courts of the city of Ibarra, the application of this prohibition error is scarce due to the lack of deep and strategic knowledge. In this sense, the general objective was to determine the importance of justice operators to adequately know the prohibition error as an exoneration of guilt, through normative and doctrinal analysis, in order to benefit both the processed persons and the administration of justice in the criminal courts of the city of Ibarra. The research method was socio-legal, inductive and analytical, and the techniques applied were documentary and interview, with which it was possible to receive direct information from professionals with experience in the subject to be investigated. It was concluded that it is important to know this legal institution in depth, to analyze it from the point of view of criminal dogma and doctrine and not only from the normative that gives us a very simple definition. If professionals had this knowledge, it would avoid violating the rights of justice, legality and innocence of the person being prosecuted and would also help in their formulation and training as professionals.